2018
DOI: 10.3390/nu10111765
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Their Neuroinflammatory Implications in Alzheimer’s Disease

Abstract: The bidirectional communication between the central nervous system (CNS) and the gut microbiota plays a pivotal role in human health. Increasing numbers of studies suggest that the gut microbiota can influence the brain and behavior of patients. Various metabolites secreted by the gut microbiota can affect the cognitive ability of patients diagnosed with neurodegenerative diseases. Nearly one in every ten Korean senior citizens suffers from Alzheimer’s disease (AD), the most common form of dementia. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
134
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(138 citation statements)
references
References 139 publications
(180 reference statements)
0
134
0
4
Order By: Relevance
“…The gastrointestinal (GI) tract of Homo sapiens contains a complex microbiome consisting primarily of bacteria, with archaea, fungi, microbial eukaryotes, protozoa, viruses, and other microorganisms making up the balance [3][4][5]7,8,16,19,25,26,89,90]. Together with human host cells this microbiome comprises the entire meta-organism whose host interactions and symbiotic associations are critical to human health and disease [4,16,18,35,72,[88][89][90].…”
Section: Overview: Human Gi-tract Microbiome and Bacteroides Fragilismentioning
confidence: 99%
“…The gastrointestinal (GI) tract of Homo sapiens contains a complex microbiome consisting primarily of bacteria, with archaea, fungi, microbial eukaryotes, protozoa, viruses, and other microorganisms making up the balance [3][4][5]7,8,16,19,25,26,89,90]. Together with human host cells this microbiome comprises the entire meta-organism whose host interactions and symbiotic associations are critical to human health and disease [4,16,18,35,72,[88][89][90].…”
Section: Overview: Human Gi-tract Microbiome and Bacteroides Fragilismentioning
confidence: 99%
“…Gut physiology (8,9) Nutrient production and absorption (10) Host development and physiology (11) Energy balancing (12) Metabolic functions (13,14) Immune system functions (15)(16)(17) Inflammatory processes (18) Neurons-brain-behavior system (19)(20)(21)(22) The majority of those studies cited here have demonstrated improvement in the clinical status of patients after targeted intervention influencing the gut microbiota. Similar studies relatively recently have led to definition of the so-called microbiome-gut-brain axis.…”
Section: Kubelkova Macela: Microbiota-gut-brain Axis 42 Box 2: Biolomentioning
confidence: 98%
“…However, the effect of probiotics supplementation on anti-inflammation or cognitive function in AD patients has not been very promising to date [201,202]. Future studies should focus on fields including proneurogenic and anti-inflammatory effects of dietary intervention and the modulation of gut microbiota and their therapeutic impact in AD models [198,203].…”
Section: Potential Therapeutic Approaches Targeting Adult Neurogenesimentioning
confidence: 99%